Gene replacement in Dictyostelium: generation of myosin null mutants. - Manstein, D J (1989)
The eukaryotic slime mold Dictyostelium discoideum has a single conventional myosin heavy chain gene (mhcA). The elimination of the mhcA gene was achieved by homologous recombination. Two gene replacement plasmids were constructed, each carrying the G418 resistance gene as a selective marker and flanked by either 0.7 kb of 5' coding sequence and 0.9 kb of 3' coding sequence or 1.5 kb of 5' flanking sequence and 1.1 kb of 3' flanking sequence. Myosin null mutants (mhcA- cells) were obtained after transformation with either of these plasmids. The mhcA- cells are genetically stable and are capable of a variety of motile processes. Our results provide genetic proof that in Dictyostelium the conventional myosin gene is required for growth in suspension, normal cell division and sporogenesis, and illustrate how gene targeting can be used as a tool in Dictyostelium.